Plutarch, two Lives, three orators: Phocion, Demosthenes and Demades - Alcalde Martín, Carlos (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2017)
In this article the fi gures of the orators Phocion, Demosthenes and Demades are analysed through the biographies that Plutarch devoted to the fi rst two personages. We try to prove that we can only approach Plutarch’s ideas on their oratory if we take his selection of the data from other authors and we contrast them with the biographer’s opinion. In addition, we have compared these data with what is encompassed in other historical and literary sources. From this detailed and complex analysis done at different levels we can extract very useful information. This will allow us to study the oratory in the biographies of Plutarch, wich might sometimes be blurred or misinterpreted when it is focused on just one personage. It is clear that Plutarch gives more importance to the personages’ conduct and character and relies on that to judge their oratory. Thus he departs himself from the assessments that he fi nds in his sources.